Do auctions improve public procurement? Evidence from the Czech Republic - Michal Kvasnicka; Rostislav Stanek; Ondrej Krcál (DANUBE: Law, Economics and Social Issues Review, 2015)
This paper explores the effect of various contract-awarding procedures in public procurement on the price of the contract. We provide a theoretical model that compares prices in different procedures and tests whether there is a significant price difference between the procedures using data from Czech public procurement. The model predicts that auctions are more efficient than negotiations given the same number of suppliers, and open procedures are more efficient than closed procedures if high-cost firms are selected for the closed procedure. In accordance with the first prediction, we find that open auctions are more efficient than open negotiations. Concerning the second prediction, we find that closed procedures are less efficient than open procedures, which suggests that procurers tend to select relatively more costly firms to participate in closed procedures. Comparing all four awarding procedures, we find that open auctions are the most efficient procedure used in the Czech Republic. We estimate that the inefficiencies due to the use of other contract-awarding procedures are substantial.
Keywords: 330; Auctions; Negotiations; Public Procurement; Contract-awarding Procedures